Blue Ocean Strategy: Business Transformation on Traditional Market Revitalisation - Lhutfi, Iqbal; Triantoro, Arvian; Kurniati, Fitrina; Hardiana, Raden Dian; Mardiani, Rika (Business Education Program of Universitas Pendidikan Indonesia, 2022)
This research was conducted to analyse the business transformation in revitalising the traditional market of Kosambi Bandung – The Hallway Space using the Blue Ocean Strategy. This study uses a descriptive qualitative research design. This study's data collection techniques were observation, in-depth interviews, and documentation review. The data analysis used in this study is a qualitative data analysis technique by analysing the statement of the interview results using the stages of data reduction, data presentation and data verification, and contextual analysis of the literature review. The result of this research is an initiation to build creative areas in traditional markets where later creative industry activists in fashion, food, art, hobbies, performing arts, and others can gather to create a new innovative ecosystem. This research concludes that the blue ocean strategy implemented in the kosambi traditional market is one of the best alternatives that can be done to revitalise traditional markets.